Variable growth responses of four tree species to climate and drought in a Madrean pine-oak forest - Marín Pompa-García; J. Julio Camarero; Cristina Valeriano; Eduardo Daniel Vivar-Vivar (Forest Ecosystems)
The tolerance of tree growth to drought in diverse mixed forests subjected to seasonal water shortage is understudied despite their ecological and economic relevance. By combining intra- and inter-annual analyses of radial growth responses to climate and drought at daily and monthly scales, different strategies to acclimate to hydroclimate variability of coexisting conifers and broadleaves were unveiled. We analyzed the growth patterns and responses to hydroclimate variability in two conifers (Pinus engelmannii, Juniperus deppeana) and two broadleaves (Quercus grisea, Arbutus arizonica) co-occurring in a Madrean pine-oak forest located in NW México. The strongest positive response to daily precipitation was found in the two conifers, but this response peaked earlier in J. deppeana than in P. engelmannii, which presented a more delayed formation of radially-enlarging tracheids. The latest negative response to temperature was found in Q. grisea, which agrees with its more delayed xylogenesis than A. arizonica. P. engelmannii presented the highest responsiveness to water shortage, driven by lower precipitation and high maximum temperatures, responding to longer droughts ending in autumn (r ​= ​0.72), whilst A. arizonica showed the lowest responsiveness to short spring droughts (r ​= ​0.39). Growth of P. engelmannii was linked to climate-atmospheric circulation patterns over the near Pacific Ocean. Overall, P. engelmannii and A. arizonica showed high growth rates and earlier growth onset, whilst J. deppeana and Q. grisea showed slower growth rates and later growth onset. The Vaganov-Shashkin growth model evidenced that winter-spring soil moisture was the key driver of growth. Under more arid conditions and more frequent and hotter droughts, pine stands could rapidly shift towards mixed pine-oak forests.